The Role of the Innate Immune System in ALS - Phani, Sudarshan; Re, Diane B.; Przedborski, Serge (Frontiers in Pharmacology, 2012)
ALS is a fatal, adult-onset neurodegenerative disease which is characterized by the death of upper and lower motor neurons. Recent studies have made clear that although motor neurons are the primary targets of the degenerative process, other cell types play key roles in the death of motor neurons. Most notably, cells of the immune system, including astrocytes and microglia have come under increasing scrutiny, after multiple lines of evidence have shown these cells to be deleterious to motor neurons. Although generally regarded as positive, both in vitro and in vivo experiments have shown that astrocytes and microglia containing mutated SOD1 are harmful to motor neurons. Several studies in ALS and other neurodegenerative diseases have shown that reactive astrocytes and microglia are capable of releasing pro-inflammatory cytokines, such as IL-1β, which are harmful to neighboring neurons. In addition, it is believed that diseased astrocytes can specifically kill motor neurons through the release of toxic factors. It has also been shown that the reduction of SOD1 in microglia may be able to slow the progression of ALS symptoms in an animal model of the disease. Although the exact pathways are not yet known, studies have suggested that motor neurons die through a Bax dependent signaling pathway. Mounting evidence suggests that neuroinflammation plays an important role in the degeneration of motor neurons. Based on these findings, anti-inflammatory compounds are currently being tested for their potential to reduce disease severity, however, these studies are only in the preliminary stages. While we understand that astrocytes and microglia play a role in the death of motor neurons in ALS, much work needs to be done to fully understand ALS pathology and the role of the immune system as it relates to the onset and progression of the disease.